No mark upon her - Crombie, Deborah (New York : William Morrow, 2012)
This mystery novel embroils Kincaid and James in the case of the puzzling drowning of a rower, a Met detective, on the Thames. It is twisting tale of psychological suspense, a story rich in deadly secrets, salacious lies, and unexpected betrayals.
Map on lining papers.
Keywords: Kincaid, Duncan (Fictitious character) -- Fiction; James, Gemma (Fictitious character : Crombie) -- Fiction; Murder -- Investigation -- Fiction; Detectives -- England -- Fiction; Mystery fiction